Global Asymptotical Stability of Delayed Impulsive Neural Networks without Lipschitz Neuron Activations (European Journal of Pure and Applied Mathematics, 2010)
In this paper, based on the homeomorphism theory and Lyapunov functional method, we investigate global asymptotical stability for a novel class of delayed impulsive neural networks without Lipschitz neuron activations. Some sufficient conditions are derived which ensure the existence, uniqueness, and global asymptotical stability of the equilibrium point of neural networks. Finally, a numerical example is given to demonstrate the improvements of the paper.